2019
DOI: 10.1136/bmjopen-2018-026324
|View full text |Cite
|
Sign up to set email alerts
|

The impact of maternal health care utilisation on routine immunisation coverage of children in Nigeria: a cross-sectional study

Abstract: ObjectiveTo examine the impact of maternal healthcare (MHC) utilisation on routine immunisation coverage of children in Nigeria.DesignIndividual level cross-sectional study using bivariate and multivariable logistic regression analyses to examine the association between MHC utilisation and routine immunisation coverage of children.SettingNigeria Demographic and Health Survey 2013.Participants5506 women aged 15–49 years with children aged 12–23 months born in the 5 years preceding the survey.Primary outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
4
11
0
Order By: Relevance
“…Our finding on the association between ANC attendance and complete childhood vaccination is consistent with studies from Ethiopia, 37 Nigeria, 38 South Africa, 39 Senegal 40 and Zimbabwe. 41 In those studies, low ANC attendance was associated with lower odds of complete childhood vaccination.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding on the association between ANC attendance and complete childhood vaccination is consistent with studies from Ethiopia, 37 Nigeria, 38 South Africa, 39 Senegal 40 and Zimbabwe. 41 In those studies, low ANC attendance was associated with lower odds of complete childhood vaccination.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with several studies in other low-income and middle-income countries (LMICs) that demonstrate that increased health communications on immunisation during MHC utilisation was significantly associated with childhood immunisation. 51 54 However, given that the sequence of MHC utilisation is ANC-SBA-PNC, the absence of a significant effect for ANC in this study does not imply that adequate ANC attendance is not associated with RI. Instead, our data suggest that other factors such as accessibility to health facilities could have a stronger association with RI than adequately attending ANC.…”
Section: Discussionmentioning
confidence: 62%
“…Also, our study found that mothers who used MHC services were significantly more likely to have full immunised children suggesting that improving MHC utilisation, especially in underserved rural communities, might be an effective strategy in achieving the IA2030 national and subnational targets. 54 However, further studies, preferably randomised controlled trials, are needed to confirm if strategies aimed at improving MHC utilisation actually improve immunisation rate. Finally, our study demonstrates the importance of reporting vaccination coverage at the local/district level to draw attention to regional inequities at that level and identify regions/districts for more targeted interventions.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Consistent with prior research on immunization coverage [ 3 , 29 , 30 ], the current study found that women who gave birth at home and other places had increased chances of experiencing measles vaccination dropout. For instance, a study on the impact of maternal health care utilization on routine immunization coverage of children in Nigeria found that ANC attendance irrespective of the number of visits had positive effects on the child being fully immunized after adjusting for covariates [ 31 ]. Additionally, in Ethiopia [ 29 ] it was reported that delivery at health facilities was significantly associated factors with full immunization, likely because some vaccines, such as BCG and OPV 0 are habitually given immediately after birth at the health facilities.…”
Section: Discussionmentioning
confidence: 99%